2018
DOI: 10.5530/phm.2018.2.16
|View full text |Cite
|
Sign up to set email alerts
|

A New Stability Indicating Ultra Performance Liquid Chromatography-PDA Method for the Estimation of Valganciclovir in Bulk and Tablet Dosage Form

Abstract: Background: The present article described about the systemic development of ultra-performance liquid chromatography (UPLC) method for the quantitative determination of valganciclovir in bulk and dosage form. The subsequent validation and degradation study was also performed. Methods: The chromatographic Separation was achieved with an HSS (100x2.1 mm, 1.8m).column with an isocratic mobile phase containing a mixture of 0.01N potassium dihydrogen orthophosphate and acetonitrile (55:45 v/v). The flow rate of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…It was performed by altering the UVspectrophotometric technique's wavelength (±2 nm). Still, there was no apparent difference in the results within the ICH guidelines [23,24]. The sample evaluation was done six times.…”
Section: Robustnessmentioning
confidence: 99%
“…It was performed by altering the UVspectrophotometric technique's wavelength (±2 nm). Still, there was no apparent difference in the results within the ICH guidelines [23,24]. The sample evaluation was done six times.…”
Section: Robustnessmentioning
confidence: 99%
“…The various methods have been used for the quantitative determination of antiviral drugs such as UV, capillary electrophoresis, and Different chromatographic methods likes GC and HPLC, LC-MS, GC-MS. In this review, authors concentrate on stability, suggesting HPLC /RP-HPLC methods for the accurately and effective development and validation of selected antiviral drugs such as, Atazanavir sulfate [35][36], Abacavir [37][38], Acyclovir [39], Adefovir Dipivoxil [41], Boceprevir [42], Baloxavir marboxil [43],Cobicistat [44], Darunavir ethanolate [45][46], Dolutegravir sodium [47][48], Didanosin [49], Efavirenz [50][51][52], Emtricitabine [53], Etravirine [54][55], Famciclovir [56][57][58], Foscarnet [59], Ganciclovir [60], Imiquimod [61], Lamivudine [62], Oseltamivir [63], Ribavirin [64][65], Simeprevir [66][67], Tenofovir [68], Valganciclovir [69][70][71][72], Zanamivir [73] and Zidovudine [74].The selective stability indicating RP-HPLC/ HPLC approaches for different antiviral drugs is summaries in Table .2…”
Section: Stability Indicating Rp-hplc/ Hplc Approaches For Different Antiviral Drugsmentioning
confidence: 99%
“…The literature search revealed that no method is known to date for the identification and quantification in the ultra‐trace range (0.83 ppm) of DMNP in the VAL active pharmaceutical ingredient and formulations by LC–MS/MS. Nevertheless, there are several published UV methods for the determination of VAL in both active pharmaceutical ingredients and finished dosage forms (Abdulrahman et al, 2021; Karthik & Sowyma, 2020; Kumar et al, 2014; Mondal, Reddy, et al, 2018). In addition, there are a few reversed‐phase HPLC methods that are also used for the determination of VAL in both active pharmaceutical ingredients and finished dosage forms (Dogan‐Topal et al, 2007; Ganorkar & Shirkhedkar, 2017; Mondal, Sunil Reddy, et al, 2018; Reddy et al, 2014; Suresh Kumar et al, 2012).…”
Section: Introductionmentioning
confidence: 99%